Biochemical and histopathological evidence on the beneficial effects of Tragopogon graminifolius in TNBS-induced colitis. (March 2015) - Farzaei, Mohammad Hosein; Ghasemi-Niri, Seyedeh Farnaz; Abdolghafari, Amir Hosein; Baeeri, Maryam; Khanavi, Mahnaz; Navaei-Nigjeh, Mona; Abdollahi, Mohammad; Rahimi, Roja
Abstract Context: Tragopogon graminifolius DC. (Compositae) (TG) has been proposed as an efficacious remedy for gastrointestinal ulcers in Iranian traditional medicine. Objective: The present study evaluates the efficacy of TG on experimental colitis and the responsible mechanisms. Materials and methods: After induction of IBD by 2, 4, 6-trinitrobenzenesulfonic acid (TNBS), rats received standardized ethanol extract of TG aerial part at 20, 30, or 50 mg/kg/d orally. After 12 d, the rats were sacrificed and the colon was removed and assessed for macroscopic and microscopic changes. Also, tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), total antioxidant capacity, myeloperoxidase (MPO), and lipid peroxidation (LPO) were measured in the colon homogenate. Result: TG extract significantly reduced macroscopic and microscopic scores of colitis with ED50 values of 23 and 39 mg/kg, respectively. MPO was significantly reduced in all plant extract groups with an ED50 value of 41 mg/kg. The ED50 values of extract for inhibition of TNF-α and LPO were 44 and 93 mg/kg, respectively. IL-1β significantly decreased by 50 mg/kg of TG extract (ED50 = 57 mg/kg). Total antioxidant power markedly increased by 50 mg/kg group (ED50 = 43 mg/kg). Discussion: TG exhibited efficacy on TNBS-induced colitis via anti-inflammatory, immunomodulatory, antioxidant, and mucosal healing properties. Conclusion: TG possesses promising healing function on colitis. Clinical trials are warranted to prove its efficacy and tolerability in IBD.